2021
DOI: 10.2138/am-2022-7991
|View full text |Cite
|
Sign up to set email alerts
|

First-principles Molecular Dynamics maps out complete mineral surface acidity landscape

Abstract: In "Interfacial structures and acidity constants (pKa) {{editor, shouldn' the a be a subscript?}} of goethite from first principles molecular dynamics siluations," authors Y. Zang, X. Lui, J. Cheng, and X. Lu (Zhang et al. 2021) apply First Principles molecular dynamics (FPMD, also called Density Functional Theory MD, DFT/MD, or ab initio MD, AIMD) to evaluate the complete set of acidy constants (pKa) of the hydroxyl groups on the most prominent goethite crystal facets. The pKa of these OH and OH+ (Sprik 2000)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Possible reactive sites for cations and anions on different surfaces can be derived based on the calculated p K a s (Table ). The sites bearing net negative charges in the normal pH range are considered to be reactive for cations and the sites with coordinated water that can be replaced with anions are considered to be reactive for anions. , It can be found that the lepidocrocite (010) surface has no reactive sites and therefore is inert. Singly coordinated sites contribute to most of the reactivities and are reactive on all surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Possible reactive sites for cations and anions on different surfaces can be derived based on the calculated p K a s (Table ). The sites bearing net negative charges in the normal pH range are considered to be reactive for cations and the sites with coordinated water that can be replaced with anions are considered to be reactive for anions. , It can be found that the lepidocrocite (010) surface has no reactive sites and therefore is inert. Singly coordinated sites contribute to most of the reactivities and are reactive on all surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of nanoconfinement on the pK a of surface OH groups has been challenging to compute with first-principles calculations. The deprotonation free energies can be computed using AIMD PMF simulations and related to the pK a of the surface OH groups (130). However, due to the computational cost, AIMD simulation cell sizes are generally limited to a thickness of water region of <2 nm; confinement effects await future quantification.…”
Section: Adsorption Kinetics and Equilibrium Constantsmentioning
confidence: 99%